Repurchase Intention of Online Fruits Boss Buah during Pandemics COVID-19 - Sheila Okthalia Audrina (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The current development of the COVID-19 virus has caused a change in offline shopping to online. This research is expected to contribute to the theory of Technology Acceptance Model (TAM) and Theory Planned Behavior (TPB), especially related to user acceptance of the marketplace and social media from Boss Buah to make repurchase intention. This study was suggest to determine the variables that affect repurchase intention on Boss Buah by using customer trust as an intervening variable. This research was conducted from May to June 2022. This study used a descriptive quantitative method with a population of consumers who had bought fruit during the COVID-19 pandemics with a sample of 224 respondents. The data is analyzed ussing Partial Least Square (PLS)-Structural Equation Model (SEM) is used to examine the model and test the hypothesis. The results showed that all variables had an influence on the repurchase intention of Boss Buah and had a significant relationship. All hypotheses are accepted and brand reputation, information quality, product delivery are successfully influenced by repurchase intention with customer trust as an intervening variable.